Changes in Corneal Endothelial Cells Morphology Due to Different Cataract Surgery Procedures: A Retrospective Study From November 2014 to November 2016 - Bariah, Ma; SY, Leong (IIUM Medical Journal Malaysia, 2020)
Introduction: The corneal endothelium is made up of an extremely thin layer of non -regenerating cells essential in keeping the cornea clear. The purpose of this study was to quantify the corneal endothelial cells morphology, visual acuity (VA) and refractive error in patients having femtosecond laser-assisted cataract surgery (FLACS) and conventional phacoemulsification surgery (CPS). Methods: Clinical data from 56 eyes were included in this study. 28 eyes had FLACS surgery and another 28 eyes had CPS. Distance VA, refractive error, corneal thickness and endothelial cells morphology were evaluated pre-operatively and at 1 month follow up. Refractive error was determined subjectively and VA was taken using Snellen chart. Specular microscope was used to measure endothelial cells morphology and central corneal thickness. Mann Whitney test and Spearman correlation analysis were used to analyse the results. Results: There were no statistically significant difference in the mean endothelial cell density (p=0.24), mean central corneal thickness (p=0.68), mean coefficient of variance (p=0.19), mean hexagonality (p=0.44), VA (p=0.72) and postoperative refractive outcome (p=0.66) between both groups. The duration of surgery was noted to have no statistically significant difference between both groups (p=0.08), while the cumulative dissipated energy and torsional time showed a significant difference between groups (p=0.01 and p<0.01 respectively). Conclusion: This study concluded that there was no significant difference in the endothelial cells morphology in patients undergoing both cataract surgeries. Both surgeries presented similar outcomes in the patients’ eyes.